മലയാളം ഫൊണറ്റിക് റീഡര്‍ - Shyamala Kumari, B. (Central Institute of Indian Languages Mysore, 1972)
Malayalam Phonetic Reader helps the learners of the language to understand the scientific pronunciation methods and patterns of the language.
Malayalam Phonetic Reader
Keywords: Malayalam; മലയാളം; ഫൊണറ്റിക് റീഡര്‍; Phonetic Reader; Phonetic Reader; Malayalam; English